Serum 25-hydroxyvitamin D level in relation to weight change and the risk of weight gain in adults of normal weight at baseline: the Norwegian HUNT cohort study - Yi-Qian Sun; Yue Chen; Xiao-Mei Mai; Adaline Heitz (BMJ Open)
Objective We sought to investigate the relationship of serum 25-hydroxyvitamin D (25(OH)D) level with weight change and the risk of weight gain in an adult population who had normal weight at baseline and were followed up for 11 years.Design A population-based prospective cohort study.Setting Nord-Trøndelag, Norway.Participants The study included 1501 adults who participated in the second and third surveys of the Nord-Trøndelag Health Study (HUNT2 (1995–1997) and HUNT3 (2006–2008)) and had a normal body mass index ≥18.5 and <25.0 kg/m2 at baseline.Primary and secondary outcome measures Relative weight change (%) was calculated as ((HUNT3 weight−HUNT2 weight)/HUNT2 weight×100). Relative annual weight change (%) was calculated as (relative weight change/follow-up years×100). Clinical weight gain was defined as relative weight change ≥5% over the 11 years, while annual weight gain was defined as relative annual weight change >1.25%.Methods Multiple regression models were used to estimate adjusted coefficients for the relative annual weight change and risk ratios (RRs) for the risk of clinical weight gain and of annual weight gain.Results Each 25 nmol/L increase in season-standardised serum 25(OH)D level at baseline was associated with a reduction of 0.05% (95% CI −0.11 to 0.01) for relative annual weight change, a 10% (RR 0.90, 95% CI 0.82 to 0.97) reduced risk of clinical weight gain, and a 19% (RR 0.81, 95% CI 0.65 to 1.00) reduced risk of annual weight gain. A statistically significant trend was evident for the risk of clinical weight gain when 25(OH)D levels were treated as a categorical variable (p=0.006).Conclusions The findings suggested an inverse association of serum 25(OH)D level with the risk of clinical weight gain in adults who had normal weight at baseline over 11 years’ follow-up.